Islamic Religious Education Project-Based Learning Model to Improve Student Creativity - Sutrisno Sutrisno; Juli Amalia Nasucha (At-tadzkir: Islamic Education Journal, 2022)
This article aims to analyze the implementation of the learning project based on PAI learning in increasing the creativity of students at school SMK Ma’rif NU Gresik. This article used a field research type of research using a descriptive qualitative approach, data collection is obtained through observation, interviews, and documentation. Furthermore, the researchers conducted the validity of the data with a credibility test model to increase persistence in research. Data analysis, namely data reduction, display, and conclusion. The subjects in this study were the head of the madrasa, Deputy Head of Curriculum, Islamic Religious Education teachers, and class students XI SMK Ma’rif NU Gresik. The results of this study are as follows; 1) The implementation of the Project Based Learning learning model in improving students' communication skills, activeness, and creativity in fiqh subjects includes learning planning which includes three stages, namely introduction, core activity, and closing; 2) The supporting factors for implementing the Project Based Learning learning model are professional teachers, positive student motivation, adequate educational facilities. The inhibiting factors are the different levels of students’ abilities and the lack of time allocation.